Bracketing subtle conformational energy differences between self-solvated and stretched trifluoropropanol1. Issue 15 (21st April 2015) - Heger, Matthias; Otto, Katharina E.; Mata, Ricardo A.; Suhm, Martin A.
<x xml:space="preserve">Abstract</x> The interconversion landscape between stretched and folded trifluoropropanol conformations is characterized by Raman jet spectroscopy and theory.